Formulations comprising extracts from primitive plant species (mosses, ferns and lichens) to treat and prevent cancers - Crawford, Sarah; Boisvert, Erin (2007)
Keywords: dept.bio; ⛔ No DOI found

Identification of novel cell components designated “tissue organizing structures”* with potential applications in cancer prevention/therapeutics, tissue bioengineering, and gene therapy - Crawford, Sarah; Herbert, Tasino; Potter, Herbert (Cancer Epidemiology and Prevention Biomarkers, 2007)
Keywords: dept.bio; ⛔ No DOI found

Tissue organizing structure and therapeutic methods - Crawford, Sarah; Potter, Herbert; Herbert, Tasino (2008)
Keywords: dept.bio; ⛔ No DOI found

Abstract A57: Lipid extract from the ostrich fern Matteucia struthiopteris displays potent anti-cancer effects in microtumors from human malignant cell lines via disruption of actin cytoskeleton - Crawford, Sarah; Penarreta, Rafaella; Diamond, Deanna (Cancer Prevention Research, 2008)
Keywords: dept.bio

Estrogen dependent growth inhibitory effects of tamoxifen but not genistein in solid tumors derived from estrogen receptor positive (ER+) primary breast carcinoma MCF7: single agent and novel combined treatment approaches. - Nobert, Gayle S; Kraak, Martha M; Crawford, Sarah (Bulletin du cancer, 2006)
While many studies have documented tamoxifen's benefits as an adjuvant therapy in the treatment and prevention of recurrent breast cancer in estrogen receptor positive (ER+) breast carcinoma, this beneficial effect may decrease with long-term tamoxifen use. This experimental study was designed to compare the cytotoxic responses of ER+ primary breast cancer solid tumors derived from the MCF7 cell line to experimental therapeutics, including genistein, tamoxifen, all-trans retinoic acid (ATRA) and parthenolide in the presence and absence of exogenous beta-estradiol. The results of this study suggest that the growth inhibitory effects of tamoxifen, were dependent on beta-estradiol levels. In contrast, the cytotoxic effects of the isoflavone soy derivative, genistein, were observed to be independent of exogenous estrogen. Moreover, combined therapy using tamoxifen and genistein produced enhanced cytotoxic effects also independent of beta-estradiol levels. Additional studies involving the use of the novel agents all trans retinoic acid (ATRA) and parthenolide produced notable tumor responses and combined effects that were also estrogen-independent. Overall, these preclinical research findings suggest possible clinical applications suggesting that genistein might be a useful clinical adjuvant, particularly in post-menopausal women in whom breast cancer occurs more frequently. Moreover, this research suggests that combined treatment approaches involving the use of tamoxifen in conjunction with agents that inhibit NFkappaB pathway signaling, such as parthenolide and genistein, warrant further study.
Keywords: *Antineoplastic Combined Chemotherapy Protocols/tu [Therapeutic Use]; *Breast Neoplasms/dt [Drug Therapy]; *Genistein/tu [Therapeutic Use]; *Neoplasms, Hormone-Dependent/dt [Drug Therapy]; *Tamoxifen/tu [Therapeutic Use]; Anticarcinogenic Agents; Anticarcinogenic Agents/tu [Therapeutic Use]; Antineoplastic Agents, Hormonal; Antineoplastic Agents, Hormonal/tu [Therapeutic Use]; Antineoplastic Combined Chemotherapy Protocols; Breast Neoplasms; Breast Neoplasms/ch [Chemistry]; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Resistance, Neoplasm; Drug Resistance, Neoplasm/de [Drug Effects]; Estradiol; Estradiol/pd [Pharmacology]; Female; Genistein; Humans; Neoplasms, Hormone-Dependent; Neoplasms, Hormone-Dependent/ch [Chemistry]; Receptors, Estrogen; Sesquiterpenes; Sesquiterpenes/tu [Therapeutic Use]; Spheroids, Cellular; Spheroids, Cellular/de [Drug Effects]; Tamoxifen; Tretinoin; Tretinoin/tu [Therapeutic Use]; antineoplastic agent; antineoplastic hormone agonists and antagonists; article; breast tumor; chemistry; dept.bio; dose response; drug effect; drug resistance; estradiol; estrogen receptor; female; genistein; human; multicellular spheroid; neoplasm; parthenolide; retinoic acid; sesquiterpene; tamoxifen; tumor cell line; ⛔ No DOI found